No child left behind, literacy challenges ahead: a focus on the Philippines - Gatcho, Al Ryanne Gabonada; Manuel, Jeremiah Paul Giron; Hajan, Bonjovi Hassan (Frontiers in Education, 2024)
The Sustainable Development Goal 4 has commenced a global mandate to provide equitable access to quality education for everyone.• In the Philippines, SDG 4 inaugurates the No Child Left Behind (NCLB) Policy.• This brief argues that while the NCLB has ensured equal access to quality literacy education, it poses socioeconomic-based challenges, declining rate of parental involvement in their children's schooling, overemphasis on standardized tests, and the lack of community involvement towards literacy programs.• The Holistic Literacy Enhancement Program (HLEP) is proposed in this paper to help address these challenges to NCLB.• HLEP presents policy implications that could assist the NCLB in more efficient and effective implementation: equitable resource allocation, parental and community engagement, and culturally and linguistically relevant assessment tools.